Intercultural Management – Trend of Contemporary Globalized World - Caganova, D.; Cambal, M.; Weidlichova Luptakova, S. (Elektronika ir Elektrotechnika, 2010)
The presented paper discusses contemporary trends in the arena of intercultural management and underlines the main concepts that both academicians and corporations should focus on. As the workplaces become more diverse, culture and intercultural management gain more importance. The importance stems from the fact that the present world is not a homogenous “monoculture” and the organizations increasingly face two simultaneously evolving issues: a) the challenges presented when companies move to new, often culturally different locations; and b) labor mobility that resulted in diverse workplaces where people from different cultural backgrounds share their work experience. This presents a twofold challenge for companies and underlines the need to focus on intercultural management.